2013
DOI: 10.1088/2043-6262/5/1/015004
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of TiO 2 nanotube arrays fabricated by the electrochemical anodization method

Abstract: Perpendicularly self-aligned TiO 2 nanotube samples of size of 3 × 5 cm 2 were fabricated by the electrochemical anodization method using a solution containing NH 4 F. Influences of the technological conditions such as NH 4 F concentration and anodization voltage were studied. It was found that NH 4 F concentration in the solution and anodization voltage significantly affect the diameter and length of a TiO 2 nanotube. The diameter and the length of a TiO 2 nanotube were observed and estimated by using scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…It is already established that with the growth of the laser energy, the melted area enlarges and therefore the real surface area of the material decreases. The observed increase of reflectance with the lowering of the surface area is in agreement with the works of other researchers 46 .…”
supporting
confidence: 93%
“…It is already established that with the growth of the laser energy, the melted area enlarges and therefore the real surface area of the material decreases. The observed increase of reflectance with the lowering of the surface area is in agreement with the works of other researchers 46 .…”
supporting
confidence: 93%
“…If the stress/strain exists on the titanium foil's surface or the crystalline facet is not favourable for etching smoothly, i.e. to release gradually the void to compensate the need of the change in the tube diameter and density, chaps would appear as observed in the literature [13,[16][17][18]. We believe that the Ti atom density is different at different crystalline facet that makes the etching rate different correspondingly.…”
Section: Resultsmentioning
confidence: 73%
“…After that, Grimes reported a new generation of vertically oriented TiO 2 nanotubes with length up to 134 μm by using various non-aqueous electrolytes [15]. From the literature one could see a problem that even though titanium nanotubes (TNTs) were well formed by electrochemical anodization, in a sufficient area of sub-square micrometers there appeared many chaps on the surface of TNTs foils [13,[16][17][18]. To the best of our knowledge, little attention has been paid to the influence of the crystalline orientation on morphological properties of titanium nanotubes, especially for forming non-chapped, well-organized TNTs array directly on titanium substrates.…”
Section: Introductionmentioning
confidence: 99%
“…We considered the substitution cases because the radius of Cu 2 + is near to that of Ti 4 + , being likely to replace the latter. For the O vacancy, it is reported to improve the optical absorption and the photocatalytic activity 39,40 . It is also reported that the addition of Cu impurities tends to create O vacancies for the charge compensation, making the optical absorption extending toward the visible-light range 22 .…”
Section: Resultsmentioning
confidence: 99%